IMPROVING THE METHODOLOGY OF USING CLOUD TECHNOLOGIES IN THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE MATHEMATICS AND INFORMATICS TEACHERS (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Education is an integral part of any society. Society cannot develop rapidly without modernizing the education system. In the modern world, education is the most important condition for the growth of social and economic well-being, the source of sustainable development of the country. Today, all the young generation prefers to use cloud services based on modern technologies. Therefore, in today's conditions, improving the ICT competence of future teachers of mathematics and informatics based on the use of cloud technologies is one of the important issues. This article talks about the development of the structure and content of ICT competence of future teachers of mathematics and informatics.